Modeling of single-fillet lap joint in Solidworks Simulation - Zdraveski, Filip; Bogatinoski, Zoran; Trajanoska, Bojana (Centre for Evaluation in Education and Science (CEON/CEES), 2016)
The aim of the work presented in this paper is to show the applicability of Solidworks Simulation module for calculation of welded structural joints. The presentation is performed through a simple model of axially loaded single-fillet lap joint. Solidworks Simulation offers several options for FEM analysis of welded joints. All reasonable options are exploited and their results are compared in this paper. The reference values are used to validate the results of FEM analysis. They are calculated based on formulas described in Eurocode 3 part 8 which refer to design resistance of fillet welds. FEM analysis is conducted in latest version of Solidworks Simulation 2015 and older version 2012. Results obtained in both versions differ from each other under same starting conditions. Finally, the paper provides recommendations for reliability of the Solidworks Simulation to be used as design tool for calculating welded joints.
Keywords: Welded structure, Design resistance of welded connections, Fillet weld, Finite element method (FEM)